IllustrisTNG plus cosmic rays with a simple transport model: from dwarfs to L* galaxies - Ramesh, Rahul; Nelson, Dylan; Girichidis, Philipp (Astronomy and astrophysics, 2025)
We used a simple model for the cosmic ray (CR) production and transport to assess the impact of CRs on the properties of z = 0 galaxies, the circumgalactic medium (CGM), and halos. To do this, we ran the ﬁrst suite of large-volume cosmological magnetohydrodynamical simulations (25 Mpc h−1 boxes) with the IllustrisTNG galaxy formation model including CR physics. We selected CR transport parameters that yielded a reasonable trade-oﬀ between realistic large-scale integrated properties and galactic CR pressure proﬁles predicted by more complex models. The resulting simulations show that at a ﬁxed halo mass, the temperature, density, or (total) pressure structure of the CGM are not strongly aﬀected when CRs are included compared to the ﬁducial TNG model. However, cosmic rays add signiﬁcant nonthermal pressure support to the halo. This suppresses the star formation activity and thus stellar masses of galaxies from dwarf to L? halos. The cosmic star formation rate density, stellar mass function, and the relation of stellar mass to halo mass are all reshaped by CRs. The galaxy sizes and halo-scale gas fractions are more mildly aﬀected, and lower gas densities in the interstellar medium inhibit the growth of supermassive black holes. The halo gas is also less strongly magnetized and less strongly enriched in metals. These diﬀerences are primarily driven by suppressed gas accretion onto halos and galaxies, and also by weaker galactic outﬂows in the presence of CRs. Our ﬁndings qualitatively agree with those of previous studies of the impact of CRs on galactic outﬂows, and they motivate the inclusion of CR physics in future large-scale cosmological simulations.